Identification of new allosteric sites and modulators of AChE through computational and experimental tools - Carlos Roca; Carlos Requena; Víctor Sebastián-Pérez; Sony Malhotra; Chris Radoux; Concepción Pérez; Ana Martinez; Juan Antonio Páez; Tom L. Blundell; Nuria E. Campillo (Taylor & Francis Group, 2018)
Allosteric sites on proteins are targeted for designing more selective inhibitors of enzyme activity and to discover new functions. Acetylcholinesterase (AChE), which is most widely known for the hydrolysis of the neurotransmitter acetylcholine, has a peripheral allosteric subsite responsible for amyloidosis in Alzheimer's disease through interaction with amyloid β-peptide. However, AChE plays other non-hydrolytic functions. Here, we identify and characterise using computational tools two new allosteric sites in AChE, which have allowed us to identify allosteric inhibitors by virtual screening guided by structure-based and fragment hotspot strategies. The identified compounds were also screened for in vitro inhibition of AChE and three were observed to be active. Further experimental (kinetic) and computational (molecular dynamics) studies have been performed to verify the allosteric activity. These new compounds may be valuable pharmacological tools in the study of non-cholinergic functions of AChE.